Using a Person-Centred Future Time Perspective Intervention to Enhance EFL Learners' Willingness to Communicate. (August 2019) - Zarrinabadi, Nourollah; Ketabi, Saeed; Tavakoli, Mansoor
This study examined the effectiveness of a person-centred future time perspective (FTP) intervention on Iranian EFL students' willingness to communicate (WTC) in English. Through one-on-one interviews with the participants, the researchers tried to build a connection between students' English learning at school and their goals in future, and to develop positive feelings about the value of speaking English. The quantitative findings followed by qualitative interview data indicated that the intervention was successful in enhancing students' WTC in English. The results showed that the intervention improved the participants' WTC by affecting their goal pursuit commitment, autonomy, feelings, and values attached to learning English. The implications of the study are discussed.